PENERAPAN METODE MIND MAPPING UNTUK MENINGKATKAN MINAT BELAJAR SISWA KELAS V SDN 1 DILEM - Kharisma, Cut Nia Erma; Kusumaningrum, Diana (Universitas Islam Raden Rahmat Malang, 2024)
This research was conducted because of the lack of interest in student learning during class. Teachers often only apply lecture-style learning methods, so students tend to be passive, bored, and uninterested. The purpose of this study was to increase the learning interest of fifth grade students at SDN 1 Dilem through the mind map method. This research is a classroom action research (CAR) by Kemmis and Mc. Taggart. Action research in the classroom consists of four phases: planning, action, observation, and reflection. This research was conducted in two cycles. The results of this study are that using mind mapping techniques can increase interest in learning. This can also be seen from the increasing percentage of learning interest in each indicator. The feeling of pleasure was 96% in cycle I, increased to 100% in cycle II, and the second indicator of interest in learning increased from 93.5% to 99%. The percentage of indicators showing attention to learning increased from 83.5% to 91.5%, and the percentage of indicators of involvement in learning increased from 74% to 83%.